Towards Whom Do Consumers Exhibit Loyalty? - Rajagukguk, Sabar Aritonang; Sofyan, Dedy; Yuniarty, Yuniarty (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2025)
Purpose – This research aims to test the effect of perceived effectiveness of loyalty programs, perceived online channel value and customer loyalty on repurchase decision.Methodology – This study employs a quantitative approach. A study involving 210 samples from ACE Hardware members who are also MISS ACE app users examined the influence of perceived online channel value and perceived effectiveness of loyalty programs on repurchase decisions, mediated by customer loyalty, using the method of SEM, with SMART-PLS software for data analysis.Findings – Both perceived effectiveness of loyalty programs and perceived online channel value significantly influence repurchase decisions, both directly and indirectly through customer loyalty. The fact that the perceived online channel value has a greater impact than loyalty programs emphasises the need to enhance the value of online platforms as the primary means of creating loyalty and driving repurchases.Originality/Novelty – This research tests four research variables that have not been studied: perceived effectiveness of loyalty programs, perceived online channel value and customer loyalty on repurchase decision.Implications – The findings suggest that ACE Hardware members value the app's functionality more than the loyalty programs in making repurchase decisions, emphasising the need for investing in app features le tailoring more market-relevant loyalty programs.